2019
DOI: 10.4155/bio-2019-0117
|View full text |Cite
|
Sign up to set email alerts
|

LC–MS Quantification of Oligonucleotides in Biological Matrices with Spe or Hybridization Extraction

Abstract: Aim: Quantitative LC–MS analysis of oligonucleotides (OGNs) in biological matrices is needed to support candidate selection of new therapeutic OGNs. Methodology & results: A set of 20 single stranded antisense oligonucleotides (ASO) and five siRNAs were extracted from plasma and tissue homogenates. Anion Exchange (AEX) SPE was selected as generic extraction approach, resulting in recoveries from plasma >70%. Extraction from tissue homogenates showed often more variation and lower recoveries. A proof of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…They also reported an intrarun decline in response when using typical ion-pairing (IP) LC–MS/MS conditions, which has been a common issue that essentially limits the application of LC–MS/MS for scaled-up ASO sample analysis in preclinical and clinical studies. During the preparation of this work, two recent studies showed improved sensitivity but still remained as proof of concept, which did not achieve optimal performance, robust applications, or metabolite quantitation. , Following the workflow of hybridization extraction and LC–MS/MS quantitation, the method presented in the current paper was thoroughly optimized with a solution to overcome the issue with signal drop and the addition of universal compatibility in most common matrixes with solid quantitative performance. The method demonstrated the capability of cross-matrix quantitation and the capability of simultaneous quantitation of parent ASO and N-1 metabolite.…”
mentioning
confidence: 99%
“…They also reported an intrarun decline in response when using typical ion-pairing (IP) LC–MS/MS conditions, which has been a common issue that essentially limits the application of LC–MS/MS for scaled-up ASO sample analysis in preclinical and clinical studies. During the preparation of this work, two recent studies showed improved sensitivity but still remained as proof of concept, which did not achieve optimal performance, robust applications, or metabolite quantitation. , Following the workflow of hybridization extraction and LC–MS/MS quantitation, the method presented in the current paper was thoroughly optimized with a solution to overcome the issue with signal drop and the addition of universal compatibility in most common matrixes with solid quantitative performance. The method demonstrated the capability of cross-matrix quantitation and the capability of simultaneous quantitation of parent ASO and N-1 metabolite.…”
mentioning
confidence: 99%
“…This allows for it to be used in conjunction with streptavidin magnetic beads to isolate a specific complementary sequence from complex samples. To date this approach has been applied to both mRNA, miRNA and therapeutic oligonucleotides (Albretsen et al, 1990; Levison et al, 1998; Berensmeier, 2006; Cantara et al, 2011; Ye & Beverly, 2011; Kim et al, 2019; Sips et al, 2019). For therapeutic oligonucleotide assays, there is evidence that this approach may bias against the recovery of closely related species such as shortmers or other metabolites (Kim et al, 2019).…”
Section: Bioanalysis Of Oligonucleotides and Their Metabolitesmentioning
confidence: 99%
“…Commercially available anion-exchange resigns, such as Clarity OTX ® and Oasis WAX ® , are one of the most popular materials used during OGN SPE. Optimized procedures that use these adsorbents give high recovery values, usually in the range of 60-90% [10][11][12][13][14][15]. However, the protocols often required additional preliminary cleaning step with the application of lysis buffer to disrupt protein binding [12,15].…”
Section: Introductionmentioning
confidence: 99%
“…Optimized procedures that use these adsorbents give high recovery values, usually in the range of 60-90% [10][11][12][13][14][15]. However, the protocols often required additional preliminary cleaning step with the application of lysis buffer to disrupt protein binding [12,15]. Moreover, some SPE procedures reported in the literature assume the application of a high concentration of salts, so they are not compatible with mass spectrometry (MS) detection or required additional desalination step [9,16].…”
Section: Introductionmentioning
confidence: 99%